102k views
4 votes
What is the sum of the geometric series E (-2)(-3)^n-1

What is the sum of the geometric series E (-2)(-3)^n-1-example-1

2 Answers

5 votes

Answer:

The sum is 40.

Explanation:

Given,


\sum_(n=1)^(4) (-2)(-3)^(n-1)

We know that,


\sum_(n=1)^(4) (-2)(-3)^(n-1)=(-2)(-3)^(1-1)+(-2)(-3)^(2-1)+(-2)(-3)^(3-1)+(-2)(-3)^(4-1)


=(-2)(-3)^(0)+(-2)(-3)^1+(-2)(-3)^2+(-2)(-3)^3


=-2* 1 - 2* - 3 - 2* 9-2* -27


=-2+6-18+54


=40

Hence,


\sum_(n=1)^(4) (-2)(-3)^(n-1)=40

User Luis Moreno
by
5.6k points
7 votes
Sum of the geometric series: S=?
S=(-2)(-3)^(1-1)+(-2)(-3)^(2-1)+(-2)(-3)^(3-1)+(-2)(-3)^(4-1)
S=(-2)[(-3)^0+(-3)^1+(-3)^2+(-3)^3]
S=(-2)[1+(-3)+9+(-27)]
S=(-2)(1-3+9-27)
S=(-2)(-20)
S=40

Answer: Third option 40
User Morteza Asadi
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.